The Influence of Life Experiences on the Development of Resilience in Older People With Co-morbid Health Problems - Windle, Gill; Bennett, Kate M.; MacLeod, Catherine; , The CFAS WALES research team (Frontiers in Medicine, 2020)
Background: Co-morbidity is a major late-life challenge with poor outcomes, yet many older people are resilient. We consider an ecopsychosocial framework of resilience to investigate this disparity. This theorises that sources of resilience may be personal, social and structural. We explored older people’s responses and reactions to significant life experiences, to understand resilience development for managing later life health challenges. Methods: We applied a two-stage, cross-sectional mixed-methods design to the Cognitive Function and Ageing Studies Wales (CFAS Wales). Participants’ defined quantitatively as resilient (high level of well-being despite co-morbidity) were identified in the wave 1 dataset. A sub-sample of the resilient participants aged 65+ were randomly selected for semi-structured interviews (N=20). Qualitative thematic analyses were both inductive and deductive. Results: The analyses revealed four primary life experiences reflecting different developmental trajectories. ‘Early years as formative’ and ‘work and employment as formative’ occurred at normative developmental stages in the life-course. In contrast non-normative life events such as loss, bereavement, illness of self and others underpinned the themes of ‘adverse events and experiences’ and ‘caring experiences’. Four potential mechanisms for resilience were central to these life experiences, reflecting reactions, actions and development: ‘character and self-identity’; ‘approach to life and insight’; ‘meaningful relationships and belonging’. Conclusions: This work contributes further theoretical insights into the ecopsychosocial resilience framework. It highlights the process of interdependence between the individual and the wider environment, suggesting how the availability and accessibility of resources and human agency (protective factors), can influence, and be influenced by, the timing of significant events and experiences. In doing so, it corroborates international healthy ageing policy which recognises resilience as important for a public health response to support older people to adjust to changes and losses experienced in later life. It highlights the importance of current and future policies and services for supporting the management of adverse events earlier in the life-course, and recommends that policies and services take a ‘long view’ on population health and well-being and consider the whole life-course, in addition to specific points in the ageing process.